An Empirical Investigation of Marketing Promotion on Malaysian Muslim Millennials Intentions to Visit Halal Tourism Destination - Ali Hanafiah; Fauziah Sh Ahmad (Universitas Mercu Buana, 2021)
Previously, the Indonesian government targeted a 16.4 % annual growth during 2014 - 2019. However, with only 10.4 % growth in 2015, undoubtedly it requires extra work to meet inbound tourist target. By 2016, inbound data shows Malaysia as the main contributor of Muslim visitor to Indonesia and Mastercard-HalalTrip 2017 report reveals Malaysia as one of the top 10 Muslim Millennial Outbound Markets from OIC countries. It makes Malaysia Muslim millennials as biggest opportunity for Indonesia tourism industry and Millennial traveler already displays as one of the fastest growing consumer segments globally. Hence, this study attempts to investigate behavioral intention of Malaysian Muslim millennials to visit Indonesia’s halal tourism destinantion. By adapting marketing promotion (MP) into TPB framework, attitude (ATT) play a role as mediating variable to assessed intention to visit (ITV). Through a quantitative research methodology, this study will collect questionnaires distributed among 294 Muslim millennials in Malaysia. Smart PLS version 3 software is used to analyze relationship prediction and hypotheses testing. The findings revealed that ATT have a mediation effect between MP and ITV. This indicates that Indonesian’s MP has a significant effect on the decision making of the Malaysian millennials to visit Indonesia as a Halal Tourism Destination. In other words, Indonesian’s MP has successfully convey the image and information of Indonesia as an attractive Halal Tourism Destination.